166k views
0 votes
Simplify.

9y+11z+7y−4z

2 Answers

3 votes
Combine Like Terms:
=9y+11z+7y+4z
=(9y+7y)+(11z+4z)
ANSWER: 16y+7z
User Gozzilli
by
6.3k points
7 votes

Answer:


16y+7z

Explanation:

Given : Expression -
9y+11z+7y-4z

To simplify : The expression

Solution :

Step 1- Write the expression


9y+11z+7y-4z=0

Step 2- Place like terms together


9y+7y+11z-4z=0

Step 3 - Add like terms and solve


16y+7z=0

The required expression in simplifying is
16y+7z

User Jake Holzinger
by
6.4k points